Cinema between media :an intermediality approach - Bruhn, Jørgen (Edinburgh university press, 2018)
Cinema has often been seen as a form between media. Early cinema borrowed heavily from traditional performing arts, like theatre and tableau vivant; and the narrative forms of literature, particularly the structure of the novel, have played important roles in shaping narrative cinema. The list of influencing forms goes on, and includes music, architecture, and painting. Following the more recent historical advents of technical media like the VCR and the DVD, and digitalisation and its effects, the notion of cinema as a mixed medium has become even more prominent within film theory. So cinema both has been and is intermedial. However, we argue that the acknowledgement of this has not affected the practice of film analysis to any great extent. This book on cinema and intermediality therefore rethinks both cinema as a form and the practice of film analysis, using concepts and analytical tools derived mainly from the fields of media theory and intermediality.